Red River Campaign Politics and Cotton in the Civil War - Johnson, Ludwell H. (Johns Hopkins University Press, 2019)
Originally published in 1958. Johnson tells the story of the Red River Campaign, which took place in Louisiana and Arkansas in the spring of 1864. In response to the demands of Union Free-Soil interests in Texas, and the need of New England textile manufacturers for cotton, an expedition was undertaken to open the way to Texas. General Nathaniel Banks conducted a combined military and naval expedition up the Red River in a campaign that lasted only from March 23 to May 20, 1864, but was one of the most destructive of the Civil War. The campaign ended in Banks's defeat at the Battle of Sabine Crossroads. This book illustrates how military operations during the Civil War were often intimately interwoven with political, economic, and ideological factors, which frequently determined the time and place of a Union offensive. The author describes the desires and opinions of the public, the press, and Lincoln's administration regarding an invasion of Texas, as well as the motivation of the officers themselves, such as Banks's aspiration for the 1864 presidential nomination. Johnson relates vividly the various battles of the expedition and the problems posed by mustering undisciplined troops, by having to procure supplies in poor country with insufficient supply lines, and by contending with bad weather and rough terrain.